2015
DOI: 10.1016/j.hjb.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Synbiotic Dietary Supplementation at Different Dosages to Prevent Vibriosis in White Shrimp, Litopenaeus vannamei

Abstract: a b s t r a c t Q 3The aim of this study was to evaluate the effect of encapsulated synbiotic (Bacillus sp. NP5 and oligosaccharide) dietary at different dosages on growth performance, survival rate, feed conversion ratio, and immune responses of Litopenaeus vannamei against Vibrio infection. The shrimps of the main treatments were fed by the diet that contained three different dosages of encapsulated synbiotic [0.5% (A), 1% (B), and 2% (C) (w/w)] with feeding rate of 5% of shrimp biomass (4 times a day). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…Despite the well-known extraordinary properties of synbiotics, additional in vivo and clinical trials are essential to demonstrate efficacy, and they need to be sufficiently powered with a randomized placebo control study design. To date, only few animal studies have been done to evaluate the effectiveness of co-encapsulated synbiotics in vivo [249][250][251]. This is particularly important when using microcapsules containing multiple bioactive ingredients, as the positive and negative interactions of synbiotics together with the encapsulation material become paramount to investigate.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-known extraordinary properties of synbiotics, additional in vivo and clinical trials are essential to demonstrate efficacy, and they need to be sufficiently powered with a randomized placebo control study design. To date, only few animal studies have been done to evaluate the effectiveness of co-encapsulated synbiotics in vivo [249][250][251]. This is particularly important when using microcapsules containing multiple bioactive ingredients, as the positive and negative interactions of synbiotics together with the encapsulation material become paramount to investigate.…”
Section: Discussionmentioning
confidence: 99%
“…The PO activity is also known as unknown substances detector in humoral non-specific immune system (Li & Xiang, 2013;Hauton, 2012). The increase of PO activity demonstrated that immunostimulant administration was able to induce the resistance and immune system of Litopenaeus vannamei towards V. harveyi infection (Zubaidah et al, 2015;Wahjunigrum et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently disease which attacked white shrimp is vibriosis caused by Vibrio harveyi (Widanarni et al, 2012). The most common ways to control the disease are using antibiotics (Defoirdt et al, 2011), SPF juvenile selection (Lightner, 2005), using normal ingredients, and sinbiotics which acts as immunostimulant (Sirirustananun et al, 2011;Zubaidah et al, 2015). The antibiotics application was prohibited nowadays because of the food security issue.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini sesuai dengan pernyataan Zubaidah et al (2015) bahwa semakin tinggi dosis Bacillus sp. yang diberikan maka laju pertumbuhan semakin meningkat.…”
Section: (Angela Mariana Lusiastuti)unclassified